Identification of a new lactoferrin-derived peptide isolated from camel milk with potential antimicrobial activity - Elnaz Khajeh; Majid Jamshidian Mojaver; Mohsen Naeemipour; Hamidreza Farzin (بیولوژی کاربردی, 2020)
Introduction: The increasing microbial resistance to existing antibiotics has increased the interest in novel antimicrobial compounds. Antimicrobial peptides (AMPs) represent an attractive alternative to classical antibiotics.Milk contains a lot of proteins, some of which have received a lot of attention, such as lactoferrin, which has antibacterial activity. The aim of this study was to investigate the antibacterial activity of a lactoferrin-derived peptide isolated from camel milk against Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa and, Acinetobacter baumannii. Materials and methods: In the present study, antibacterial peptides in milk lactoferrin were identified using bioinformatics tools. Trypsin I peptide was synthesized. Then, the toxicity of the peptide on the cell line was investigated by the MTT method. The antibacterial properties of trypsin I was evaluated on four pathogenic bacteria, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii and, Streptococcus pyogenes. Results: The results showed that the peptides had no lethal effect on the cell line tested. The MIC results of trypsin peptide for Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii and, Streptococcus pyogenes were 7.81, 15.62, 125 and 250, respectively. Conclusion: Antimicrobial peptides have received much attention in recent decades due to their appropriate properties and characteristics such as rapid lethality, a wide range of activity and, also the rare development of cases of drug resistance. According to the observed results of this study, the antibacterial properties of the compounds isolated from this study can be a good alternative to replacement with common antibiotics.